Quantum Key Distribution Protocol for Knapsack Cryptosystem - Sarathi Goswami, Partha; Chakraborty, Tamal; Chattopadhyay, Abir (International Journal of Computer Sciences and Engineering, 2025)
The major threat in data communication in present day is security. To reduce the threat caused in the communication channel quantum cryptography is emerging as a replacement to its classical counterpart. This paper focuses on a quantum key distribution protocol for the knapsack cryptosystem using a one-way trapdoor function by qubit rotation. The protocol exploits a qubit in superposition state for a single bit message communication. The security of the protocol is owing to the fact that any random quantum state cannot be replicated.